Biology : - Avila, Vernon L. (Jones and Bartlett, 1995)
This textbook covers the main topics required by GCSE syllabuses in Human Biology. It will also supplement GCSE Biology courses and provide an excellent basic reference for all students needing a grounding in Human Biology. Each unit is dealt with in a double-page spread with text on the left hand page and diagrams on the right allowing each topic to be easily assimilated. The features include: simply worded text with clear explanations of important technical terms; detailed glossary; and vocabulary and comprehension tests using both text and diagrams to reinforce understanding.